(untitled) (University of Thi-Qar Journal for Engineering Sciences, 2011)
Resistible composites have been suggested to be used instead of carbon steel pipes to overcome a number of common problems during commercial applications, especially the problem of fixing dead-beat carbon steel pipes within these systems. The new composites used are resistible materials of unsaturated polyester sponsored with glass fiber and aluminum honeycomb. Mechanical properties of resistible composites have been studied using ASTM in order to find the best conditions to create a system of pipes. It have been seen clearly that the best concentration of aluminum powder is 3٥ % of the composite mixture, which represent the most suitable mechanical properties. Also, it was found that aluminum honeycomb samples were a very good mechanical properties suitable for certain applications.